Government delivery system: the effectiveness of local authorities in Perak - Mohamed Osman, Mariana; Bachok, Syahriah; M. Bakri, Nurul Izzati (2014)
Local authorities’ performances are important in positive public perception to the overall government structure. In developing countries, improving the quality of government delivery system is quite challenging, but effective delivery systems are crucial in achieving the people’s satisfaction level. A total of 250 respondents in selected 10 local authorities participated in the questionnaires survey. The survey was to assess the level of performances performed by Local Authorities in Perak. Several recommendations proposed to strengthen local authorities’ performances and improved public satisfaction level.